Predação de pequenos mamíferos por suindara (Tyto alba) e seu papel no controle de reservatórios naturais de hantavírus em uma área periurbana do município de Uberlândia, Minas Gerais, Brasil - Magrini, Leandro (2006)
Small mammals, especially rodents, are the main prey of the barn owl and its diet is considered an accurated reflex of the local fauna composition and populational flutuations. The principal objectives of this study were to inventory the species of small mammals in the outskirts of the Municipality of Uberlândia, MG, based on the analysis of regurgitated pellets of barn owls and to compare the frequency of murid rodents in the diet with the abundance of these prey in rural and urban areas. Since in this region there is a great incidence of hantaviruses, we also evaluate the importance of the barn owl in the control of populations of rodents that transmit the hantavirus. Pellets were collected in four different moments, from May 2003 to August 2005, under a shelter used by a barn owl couple. Data on richness and relative abundance of rodents in Uberlândia used as an indicator of prey availability for barn owls were obtained through three semestrial trap samplings conducted by the Centro de Controle de Zoonoses (CCZ). In total, 736 food items were found by the analysis of 118 fragments and 96 whole pellets. The total number of taxa identified in the diet of the barn owl was 13, and it was necessary to examine 76 (35.5%) of the 214 samples until all these were represented. The number of items found by pellet varied from one to 10 and it did not differ along the three years of study, with a general mean of 4.19 prey by pellet. Mammals were the principal prey consumed by the barn owl in the study area (86.0% of food items), represented mainly by murid rodents (85.2%). Among mammals, prey were represented by one species of marsupial (Gracilinanus agilis) and seven species of rodents, with Calomys tener (70.9%) and Bolomys lasiurus (6.7%) being the most frequent. Birds and insects constituted 7.9% and 6.1% of the total prey, respectively. The proportion of murid species consumed by the barn owl differed from that observed in the trap samplings, and the species Calomys expulsus, C. tener and Oligoryzomys nigripes were consumed more frequently than expected. The analysis of regurgitated pellets of barn owl was useful for obtaining information on diversity and populational features of small 3 mammal species. Although restricted to a single place and based on few individuals, the present study allowed to inventory seven of the eight species of murid rodents collected by the CCZ in Uberlândia. The comparison among the relative frequencies of murid rodent species in the diet of the barn owl and the abundance of these prey in the environment suggests the existence of dietary selectivity. However, it should be pointed out that the abundance of prey in the field can not correspond to their real availability to a given predator once behavioral and morphologic features may result in interspecific differences in vulnerability to predation. The second more consumed rodent species in the study area was B. lasiurus, the main hantavirus reservoir in the Cerrado biome. In this way, the barn owl seems to play an important role in the control of the population of this species in the area, contributing to avoid the increase of the number of cases of hantaviruses.